Self-organizing techniques in ultra-dense wireless network - Jian-dong LI; Wei TENG; Min SHENG; Chao XU (Tongxin xuebao)
Network densification was one of the main ways to deal with the challenge of supporting 1 000 times higher capacity in 5G networks. Wherein, a single node needs to configure and optimize more than 2 000 parameters. Therefore, novel self-organizing network (SON) would be the inevitable technique for wireless networking, where decision makers were enabled with the ability of perceiving the dynamic network situation and meanwhile, autonomously discovering as well as configuring network resources. With the aid of this promising technique, users' demands and network resources could be well matched and furthermore, the capacity of networks could be significantly improved. The trend of dense development in wireless communications was discussed. Then, the potential challenges and required new properties was analyzed when util-izing SON in ultra-dense wireless networks. Meanwhile, two typical use cases were depicted. Finally, for future ultra-densely deployed wireless networks, the possible development prospect and direction of SON were briefly presented.